PENGARUH BIG FIVE PERSONALITY TERHADAP KINERJA PEGAWAI MELALUI BUDAYA ORGANISASI - shinta dewi ambarwaty yusuf (Balitbangda Provinsi Jambi, 2021)
So far, the culture of civil servants is still at issue especially supported by personalities that are in the public spotlight in providing services to the community. The purpose of this study was to determine the description of a person's personality through Big Culture, Organizational Culture Overview and Balitbangda Employee Performance in Jambi Province and determine the relationship of influence between big five personality and organizational culture on employee performance both simultaneously and partially and to test organizational culture as a moderating variable on the influence Big five personality on performance. This study uses survey research techniques, census sampling techniques that are all Balitbangda employees as samples and data analysis is done descriptively and perivikatip. Descriptively describe the variables studied from the variables without testing. Perivikatip examine the relationship of influence between the independent variable and the dependent variable. The results of data processing indicate that descriptively Big Five Personality, organizational culture and performance are in the quite good category. The perivikatip test shows that there is a significant significant influence on the Big Five Personality of organizational culture and has a positive relationship. Organizational culture has a positive and significant influence on organizational performance, Big Five Personality has a positive and significant influence on performance. There is a significant mediating effect of the interaction of the Big Five Personality and Organizational Culture on the influence of the Big Five Personality on the Performance of Balitbangda Jambi Province Employees